2020
DOI: 10.1093/ehjci/jeaa261
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular myocardial work: proof-of-concept for non-invasive assessment of right ventricular function

Abstract: Aims Right ventricular myocardial work (RVMW) is a novel method for non-invasive assessment of right ventricular (RV) function utilizing RV pressure–strain loops. This study aimed to explore the relationship between RVMW and invasive indices of right heart catheterization (RHC) in a cohort of patients with heart failure with reduced left ventricular ejection fraction (HFrEF), and to compare values of RVMW with those of a group of patients without cardiovascular disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(84 citation statements)
references
References 29 publications
3
81
0
Order By: Relevance
“…MW has already been investigated recently in right ventricle (RV) and seems to correlate better than other conventional echocardiography parameters with invasive stroke volume and stroke volume index [55]. However, this method needs further research and development to estimate the real global RV performance because we are at the moment restricted to include only the segments that we can appreciate from 4C view; 4D echocardiography may give an answer to this problem.…”
Section: Right Ventricle Assessmentmentioning
confidence: 99%
“…MW has already been investigated recently in right ventricle (RV) and seems to correlate better than other conventional echocardiography parameters with invasive stroke volume and stroke volume index [55]. However, this method needs further research and development to estimate the real global RV performance because we are at the moment restricted to include only the segments that we can appreciate from 4C view; 4D echocardiography may give an answer to this problem.…”
Section: Right Ventricle Assessmentmentioning
confidence: 99%
“…As previously described, non-invasive MW indices are currently measured with a software validated for the measurement of LV MW. Recently, a proof-of-concept study showed the feasibility of right ventricle (RV) MW indices measurement in a small population of HFrEF [ 65 ]. In addition to the reduction of RV GWI, GCW, GWE and increase of GWW in HF patients compared to controls, they demonstrated that RV GCW is the only echocardiographic parameter associated with invasively measured stroke volume [ 65 ].…”
Section: Emerging Areas Of Applicationmentioning
confidence: 99%
“…Recently, a proof-of-concept study showed the feasibility of right ventricle (RV) MW indices measurement in a small population of HFrEF [ 65 ]. In addition to the reduction of RV GWI, GCW, GWE and increase of GWW in HF patients compared to controls, they demonstrated that RV GCW is the only echocardiographic parameter associated with invasively measured stroke volume [ 65 ]. Therefore, MW seems to also be able to provide an all-around evaluation of the RV function, integrating information on contractility, dyssynchrony and pulmonary pressure, and overcoming the limitations of other standard parameters such as TAPSE, RV GLS or fractional area change [ 66 ].…”
Section: Emerging Areas Of Applicationmentioning
confidence: 99%
“…e outcomes are encouraging, but they rather indicate a dependence of stroke volume on the variations in skin warming, age, and pulse pressure of the patient; hence, it is not an automatic technique of stroke volume quantification. In [8], another technique has been suggested particularly for noninvasive stroke volume estimation via indirect myocardial work evaluation. Nonetheless, the basic concept is based on echocardiography that is not appropriate for continuous assessment.…”
Section: Introductionmentioning
confidence: 99%